Importance Of Leadership In Architectural Education - (:unkn) unknown (Iated-Int Assoc Technology Education A& Development, Lauri Volpi 6, Valenica, Burjassot 46100, Spain, 2013)
People are social living being that live in groups. Leadership is needed for collecting people around a group and reaching both personal and common objectives. One of the more useful definitions of leadership is the process of influencing others to facilitate the attainment of organizationally relevant goals. Architects require a high degree of personal skills and social competence to lead. Whether it is the partners involved or the tradesperson who will work on implementing the building project, the architect will come into contact with a large number of professional partners in the course of the project. When a large number of people are working on a project, a high level of successful teamwork is required. A high level of social competence is required to work in a team and to be able to deal with all kinds of people. Architects are leaders of both the architectural design team and generally the design team. In NAAB Conditions for Accreditation for Professional Degree Programs in Architecture 2004 Edition, student performance criteria were given as a list of 34 items, without grouping. Leadership was the 32nd. item in the student performance criteria list. In 2009 edition,, leadership. is defined as;, Understanding of the techniques and skills architects use to work collaboratively in the building design and construction process and on environmental, social, and aesthetic issues in their communities.. The purpose of this study is emphasizing the importance of gaining architect candidates' leadership qualities during their education. This study is based on a research investigating program curricular framework of twenty architectural schools from different parts of the world. The research comprises an investigation over leadership training courses in architectural programs. If there are any courses through leadership education or any other courses aiming to gain architect candidates' leadership qualities is investigated.
Keywords: Leadership; Architect; Architectural Education; Architecture; Liderlik; Mimar; Mimarlık; Mimari Eğitim